Leisure-time physical activity across adulthood and biomarkers of cardiovascular disease at age 60–64: A prospective cohort study. (February 2018) - Elhakeem, Ahmed; Murray, Emily T.; Cooper, Rachel; Kuh, Diana; Whincup, Peter; Hardy, Rebecca
Abstract: Background and aims: This study examined associations between leisure-time physical activity (LTPA) across adulthood (from age 36) and cardiovascular disease (CVD) biomarkers at age 60–64. Methods: LTPA was reported by study participants from the MRC National Survey of Health and Development at ages 36, 43, 53 and 60–64 (n = 1754) and categorised as inactive, moderately active (1–4/month) or most active (5+/month) at each age. Linear regression was used to examine associations between a cumulative adulthood LTPA score (range = 0–8), and change in LTPA between ages 36 and 60–64 (i.e. always inactive, became inactive, became active, always active) and inflammatory [C-reactive protein (CRP), interleukin-6 (IL-6)], endothelial [tissue-Plasminogen Activator (t-PA), E-selectin] and adipokine [leptin, adiponectin] measures extracted from overnight fasting blood samples at age 60–64. Results: The more active a participant was over adulthood, the better their biomarker profile, e.g. fully-adjusted difference in t-PA (both sexes) and adiponectin (women) per unit increase in the LTPA score (95% confidence interval) = −2.2% (−3.6; −0.8) and 2.0% (0.2; 3.8). Those that became active at age 60–64 showed slightly healthier biomarker profiles than those that became inactive [e.g. fully-adjusted difference in IL-6 = −9.9% (−23.9; 4.1) vs. −3.8% (−12.4; 4.8)], although the best profiles were seen for those always active [IL-6: −15.0% (−24.2; −5.7)], when compared with the always inactive group. Conclusions: Greater accumulation of LTPA across adulthood was associated with a more favourable CVD biomarker profile in early old age. Earlier uptake and long-term maintenance of LTPA may provide the greatest benefits for CVD prevention. Highlights: Greater LTPA over 28 years related to healthier atherosclerotic biomarker profiles. Taking up LTPA related to better biomarker levels than staying inactive over life. Differences in biomarker levels by LTPA were only partly mediated by body size. Earlier uptake and long-term maintenance of LTPA may provide greatest benefits.